A DNA-nanoassembly-based approach to map membrane protein nanoenvironments - Ambrosetti, Elena (Karolinska Institutet, 2021)
Most proteins at the plasma membrane are not uniformly distributed but localize to dynamic domains of nanoscale dimensions. To investigate their functional relevance, there is a need for methods that enable comprehensive analysis of the compositions and spatial organizations of membrane protein nanodomains in cell populations. Here we describe the development of a non-microscopy based method for ensemble analysis of membrane protein nanodomains. The method, termed NANOscale DEciphEring of membrane Protein nanodomains (NanoDeep), is based on the use of DNA nanoassemblies to translate membrane protein organization information into a DNA sequencing readout. Using NanoDeep, we characterised the nanoenvironments of Her2, a membrane receptor of critical relevance in cancer. Importantly, we were able to modulate by design the inventory of proteins analysed by NanoDeep. NanoDeep has the potential to provide new insights into the roles of the composition and spatial organization of protein nanoenvironments in the regulation of membrane protein function.

The methodology is described in the preprint article (see publications list).

The methodology for this dataset is available in the preprint (see publication list)

Software for data collection:
Biacore T200 System Control software, NextSeq control software
Software for data analysis:
BIAevaluation v3.0, GraphPad Prism v8.2.1, Fiji ImageJ v1.0, Illumina Sequencing Analysis Viewer software, Python v3.8.0.

De flesta proteiner vid plasmamembranet är inte jämnt fördelade men lokaliseras till dynamiska nanodomäner. För att undersöka deras funktionella relevans finns det ett behov av metoder som möjliggör omfattande analys av kompositionerna och rumsliga organisationerna av membranprotein-nanodomäner i cellpopulationer. Här beskriver vi utvecklingen av en icke-mikroskopibaserad metod för ensembleanalys av membranprotein-nanodomäner. Metoden, benämnd NANOscale DEciphEring of membrane Protein nanodomains (NanoDeep), baseras på användningen av DNA-nano assemblies för att översätta information om membranproteinorganisation till en DNA-sekvenseringsavläsning. Med hjälp av NanoDeep karakteriserade vi nano-miljöerna hos Her2, en membranreceptor av kritisk relevans vid cancer. NanoDeep har potential att ge nya insikter om rollerna för sammansättningen och den rumsliga organisationen av proteinnanomiljöer i regleringen av membranproteinfunktionen.

Metoden finns beskriven i preprint (se publikationer).

Metoden finns beskriven i preprint (se publikationer).

Mjukvaror för datainsamling:
Biacore T200 System Control software, NextSeq control software


Mjukvaror för dataanalys:
BIAevaluation v3.0, GraphPad Prism v8.2.1, Fiji ImageJ v1.0, Illumina Sequencing Analysis Viewer software, Python v3.8.0.
A DNA-nanoassembly-based approach to map membrane protein nanoenvironments
Keywords: Amino Acids, Peptides, and Proteins; Aminosyror, peptider och proteiner; Cell Membrane; Cellmembran; NanoDeep; NanoDeep; Biophysics; Biofysik; Molecular Biology; Molekylärbiologi